TRACKING LIPID CHANGES IN BLOOD TO PREDICT ONSET OF CANCER - AMRUTA SONAWANE; PUSHPA ROBIN (International Journal of Pharma and Bio Sciences, 2014)
Cancer the dreaded disease continues to evoke fear despite great advances in medical research. The passion that drives cancer research is to find an early harbinger of the disease. Early detection in the form of a biomarker can be used to predict onset of, identify the presence of a tumor, and determine its stage, subtype, and ability to respond to therapy. Biomarkers are therefore an invaluable tool. Protein based biomarkers have been identified but have fallen short of their expectations. Gene based markers are in their infancy. Alterations in lipid metabolism have been shown to be positively related to onset of various cancers. To establish the role of lipids in cancer, studies have focused on the enzymes, metabolites and other biomolecules related to lipids. In this review an attempt has been made to highlight the progress in research done in this area.